ANALISIS OF THE IMPLEMENTATION CHARACTER EDUCATION AT SMP 1 WONOGIRI AT ACADEMIC YEAR 2012/2013 - -, Sugiyarno (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
This study aims to : (1) determine the implementation of character education in SMP Negeri 1 Wonogiri academic year 2012/2013. (2) determine the constraints that arise in the implementation and how to overcome them in the implementation of character education in SMP Negeri 1 Wonogiri academic year 2012/2013.The research was conducted at SMP Negeri I Wonogiri. This study used a qualitative approach in the form of discreptive. Sources of data obtained from three sources, namely (1) the event, (2) the informant, (3) documents or written sources. Data was collected by: (1) observation / observation. (2) interview (3) Teaching documents (content analysis), (4) questionnaire. Purpusive sampling using sampling and sample techniques. Examination of the validity of the data by using the constancy of observation and triangulation of data. The results were analyzed using intraktif technical analysis (1) data reduction, (2) presentation of data, (3) drawing conclusions / verification.Research results are (1) the implementation of the implementation of the character of students in learning social studies in SMP Negeri 1 Wonogiri is already running but not maximum, (2) the constraints that emerged was the lack of implementation of teacher learning model based on the characters, the lack of a policy on the assessment of character education in learning, and the weak awareness and willingness of students in the application of character values in daily life.Â Keywords: character education, social studies learning